Diabetes Mellitus and the Possibility of Developing Dementia - Kumar, S. Nelson; Basha, V. Wazeed; Sireesha, C.; Gnanaprakasam, G. Jacob; Kalyan, M. Pavan; Padmakar, Somanaboina (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Dementia and cognitive dysfunction have many causes. There is strong evidence that diabetes mellitus (DM) increases the risk of cognitive impairment and dementia. A prophylactic approach, optimal glycaemic control, and identification of diabetic risk factors are essential to preventing cognitive complications. Objective: The main objectives of this study are to assess the severity of dementia by using the Clinical Dementia Rating scale (CDR), and the effect of longevity of diabetes mellitus on the severity of dementia. Method: It is a Hospital-based prospective observational study, in which the patients were enrolled into the study after taking an informed consent form from them based on the inclusion and exclusion criteria. Results: Out of 80 patients, 62(77.5%) were suffering with dementia and 18(22.5%) were found to be normal. The diabetes patients included in this study had a duration of diabetes ranges from 6 to 30 years. Using the CDR scale, 24 of them (30%) were diagnosed with moderate dementia. Conclusion: According to our findings, we emphasize the need to consider DM as a potential risk factor for dementia.